2013
DOI: 10.5006/0990
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Prior Cold Work on Hydrogen Trapping and Diffusion in API X-70 Line Pipe Steel During Electrochemical Charging

Abstract: The effect of prior cold work (10, 20, and 40% reduction in thickness) on hydrogen diffusion and trapping was investigated using both Devanathan permeation and thermal desorption methods. The first rise transient during diffusion-controlled permeation marks the slowest Deff (1.8×10−7 cm2/s in as-received API X-70 steel), which is indicative of the greatest degree of trapping by both irreversible and reversible traps. Faster Deff during all subsequent decay and rise transients (3.0 to 4.2×10−6 cm2/s in as-recei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(35 citation statements)
references
References 79 publications
1
34
0
Order By: Relevance
“…400 nm in thickness was electroplated on the chemically etched surface. It is reported that plate thickness is influenced on an amount of absorbed hydrogen [21,22]. According to the result of Ha et al [22], thinner foils less than 448 m did not follow Fickian diffusion behavior.…”
Section: Samplementioning
confidence: 89%
“…400 nm in thickness was electroplated on the chemically etched surface. It is reported that plate thickness is influenced on an amount of absorbed hydrogen [21,22]. According to the result of Ha et al [22], thinner foils less than 448 m did not follow Fickian diffusion behavior.…”
Section: Samplementioning
confidence: 89%
“…where N L is the density of interstitial sites in the steel, D L is the lattice diffusion coefficient of hydrogen; D eff is the effective hydrogen diffusion coefficient in the presence of traps; E b is the hydrogentrap binding energy, which can be evaluated from the TDS spectra [44,[53][54][55][56][57][58][59][60]; R is the universal gas constant; and T is the absolute temperature. The density of traps measured by means of Eq.…”
Section: Introductionmentioning
confidence: 99%
“…(3) pertains only to reversible traps under conditions such as those used in the present research where all the irreversible traps have been filled. This model was derived from the following equation [19,58,59], by assuming one dominant reversible trap:…”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13][14] This technique has been applied to the measurement of hydrogen absorption into metallic materials and confirmed to be quite useful for in-situ evaluation of the amount of hydrogen absorption into metals and alloys. [15][16][17] Normally, in the Devanathan-Stachurski permeation technique, two identical vessels in each of which electrochemical measurements can be performed with a conventional threeelectrode-system are prepared, and then a thin metallic film, "membrane", is placed between the vessels and tightened up with them. In this study, two identical glass vessels were used; one of the glass vessels used for the hydrogen-entry side is referred to "H-entry-side" cell, and the other is for the hydrogen-withdrawal side to "H-withdrawal-side" cell, as shown in Fig.…”
Section: Electrochemical Set-upmentioning
confidence: 99%